The Climate-Smart Villages (CSV) of Olopa as a local innovation platform for scaling ecosystem-based adaptation in Guatemala - Martinez Salgado, Jesus David; Borrayo, Andrea Surama; Claudia, Lopez; Castellanos, Andrea; Martinez Baron, Deissy (2025)
The municipality of Olopa (Guatemala) is located in the Central American Dry Corridor, a region characterized by irregular rainfall, high susceptibility to climate variability (FAO, 2019), and classified as highly vulnerable to climate change according to IPCC models (2013). In this territory, the recurrence of events such as droughts has driven farmers to intensively exploit environmental resources to maintain and/or increase their income and food security (Calvo-Solano et al., 2018). However, this has resulted in a vicious cycle in which the inefficient use of environmental resources progressively reduces the climate resilience of agri-food systems (FAO, 2023), decreasing farmers’ incomes and preventing them from improving their livelihoods. The Climate-Smart Villages (CSV) (Aggarwal et al., 2018) has been established in Olopa since 2015. It integrates research for development to address specific agroclimatic challenges faced by rural producers. This approach aims to strengthen communities’ capacity to reduce their climate vulnerability by increasing their knowledge and adopting informed and sustainable measures related to soil and water conservation and management, biodiversity protection, the use of local agroclimatic information, emission reduction strategies, and adaptation plans tailored to the needs of families and communities through a participatory and inclusive process.